Analisis Perencanaan Pembagian Beban Dan Instalasi Listrik Pada Hotel Golden Tulip Di Kota Pontianak - ., Edi Ridwan (Faculty of Engineering, Universitas Tanjungpura, 2015)
One of building sector which is developing in Pontianak city is the raise of hotels in the center city. Hotel needs large enough electric energy. It’s proved by the used of transformator capacity, till 1250 KVA and the use of genset as big as 1000 KVA. This must be followed by a good and efficient electric distribution to get high electric energy supply. The hotel building that become a research object in Pontianak city is located in Jl. Teuku umar is Golden Tulip. It stand on 11 floors that consume big enough electric energy. This hotel has had a good distribution system, effectif and efficient instalation such as balance dividing load, safe and standart electric instalation, PUIL 2000 and professional electric system to minimize the waste of electric energy while distribution because of the loses power. Based on accounting result, data analiz, dividing load and electric instalation in hotel Golden Tulip Pontianak must be divided and categoried spread evenly between stand by load and unstand by load to get the balance dividing load, otherwise on the measuring result in the basemant floor until five floor, there is unbalance load that cause by the unspread evenly load categories to get the safe MCB result, MCCB and grounding cabel is different with planning result. This is happened because 1 feeder pull for 3 different panel in basemant floor, 1st floor and 2nd floor. Same cases with the 3rd floor panel, 4th floor and 5th floor only need 1 feeder pull. Based on planning analize result for the effeciency distribution of electric power can be done by 1 feeder pull directly to each panel / floor. Keyword : Load dividing, electric instalation, PUIL 2000.